PENGGUNAAN LEMBAR PEMANTAUAN NUTRISI OLEH KELUARGA PASIEN CHRONIC KIDNEY DISEASE YANG MENJALANI HEMODIALISA - Syahputri, Lea Agustin; Yustisia, Nova; Hasymi, Yusran (JURNAL KEPERAWATAN MUHAMMADIYAH BENGKULU, 2023)
CKD (Chronic Kidney Disease) is a damage to the renal kidney which will affect the work function of the kidneys, namely the inability of the kidneys to remove toxins and blood waste. End-stage CKD patients require renal replacement therapy, namely hemodialysis. Routine hemodialysis therapy in patients can be at risk of malnutrition, so regular monitoring of the patient's nutritional status is needed. This study aims to determine the description of the use of nutritional monitoring sheets by families in CKD patients in the Hemodialysis Room at M.Yunus Hospital. Researchers used quantitative research methods, using data analysis with descriptive techniques. This research was conducted in the Hemodialysis Room of Dr. M.Yunus Hospital Bengkulu City, the research time was conducted for 1 month, the variables in this study were nutritional monitoring in CKD patients which included time, meal frequency, composition, and volume. The population in the study amounted to 63 people and the number of samples taken was 54 people, but the number of willing respondents was only 30 people. The results showed that the fulfillment of patient nutrition was not in accordance with the nutrition monitoring sheet, as many as 61.3% (18 people), while patients who fulfilled nutrition according to the nutrition monitoring sheet were only 38.7% (12 people). The results of the study are expected to provide information and input as well as a source of basic data to continue the development of similar studies.